Extreme field confinement in zigzag plasmonic crystals. (22nd September 2020) - Park, Nu-Ri; Kim, Han-Na; Jin, Young-Ho; Kim, Moohyuk; Lee, Keun-soo; Kim, Myung-Ki
Abstract: We propose extreme field confinement in a zigzag plasmonic crystal that can produce a wide plasmonic bandgap near the visible frequency range. By applying a periodic zigzag structure to a metal–insulator–metal plasmonic waveguide, the lowest three plasmonic crystal bands are flattened, creating a high-quality broadband plasmonic mirror over a wavelength range of 526–909 nm. Utilizing zigzag plasmonic crystals in a three-dimensional tapered metal–insulator–metal plasmonic cavity, extreme field confinement with a modal volume of less than 0.00005 λ 3 can be achieved even at resonances over a wide frequency range. In addition, by selecting the number of zigzag periods in the plasmonic crystal, critical coupling between the cavity and the waveguide can be achieved, thereby maximizing the field intensity with an enhancement factor of 10 5 or more. We believe that zigzag plasmonic crystals will provide a powerful platform for implementing broadband on-chip plasmonic devices.